An Analysis of Student Learning Style in Learning English in MI Mardhatillah Rambutan - Menik Irawati; Tiara Eliza; Melisa Novianty (Journal of Research in Social Science and Humanities, 2025)
This research was aimed to analyze the learning styles of students in grades 4,5, and 6 of MI Mardhatillah in the context of English learning. The method used in the study was qualitative. The result of the study showed that visual (14%), Auditory (29%), and Kinesthetic (57%). Therefore, student MI Mardhatillah rambutan like to use kinesthetic as their learning style in learning English. Although the kinesthetic learning style is dominant, some students also show a tendency towards auditory and visual learning styles. Meanwhile, research identified several student learning difficulties, such as: lack of motivation, basic mastery of English, and limited supporting facilities at school. To overcome these challenges, teachers and schools are advised to create an environment that supports student learning motivation, paying special attention to the student learning style system.